Virtue Ethics in Medical Practice during the COVID-19 Pandemic - Karel Sládek (Acta Universitatis Carolinae Theologica, 2022)
The article aims to reflect the medical virtue ethics as applied to situations related to the COVID-19 pandemic. The method of processing uses deduction, by which the article points out the use of the generally defined cardinal and theological virtues in terms of specific attitudes and concrete situations. The practical output of the article is the usability of these reflections in the prevention and therapy of stress, including burnout syndrome and post-traumatic stress disorder. Stress was a reaction commonly experienced often and in various degrees during the new and unforeseen conditions of the pandemic. The article emphasises the importance of virtue ethics as a part of contemporary bioethics.